PENGARUH GAJI, PROMOSI JABATAN, SUPERVISI TERHADAP KEPUASAN KERJA PADA PT . OVELA INDONESIA - Sitio, Vera Sylvia Saragi (Feb Universitas Dirgantara Marsekal Suryadarma, 2019)
The company must provide satisfaction for all employees who work in the company, both from the top, middle and to the executor level. Through job satisfaction for all employees can determine the attitude of employees towards their work. This study aims to determine the effect of salary, promotion and supervision on employee satisfaction. The total population in this study amounted to 107 employees, the sample in this study amounted to 84 respondents with a purposive sampling method. The research method used is multiple linear regression analysis. The results showed that there was a significant effect of salary, promotion and supervision on job satisfaction with a determination coefficient value of 97%, while the rest was influenced by other variables not explained in the model.Keywords: Salary, Promotion, Supervision, Job Satisfaction